2014
DOI: 10.3168/jds.2014-8248
|View full text |Cite
|
Sign up to set email alerts
|

Use of a direct-fed microbial product as a supplement during the transition period in dairy cattle

Abstract: Two studies were conducted. The objective of the first study was to assess the effects of a direct-fed microbial (DFM) product on dry matter intake, milk yield, milk components, disease incidence, and blood metabolites in dairy cattle. The objective of the second study was to assess the effects of DFM on apparent total-tract nutrient digestibility (ATTD). One hundred twenty primiparous and multiparous Holstein cows housed in a tiestall facility at the University of Guelph were used in study 1, and a subset (21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 51 publications
(68 reference statements)
0
11
0
1
Order By: Relevance
“…Feeding with the preparation was started three weeks before the calving and ended 10 weeks after the calving. The results revealed that DFM had a positive effect on digestibility of the fodders in the digestive tract (Al Zahal et al, 2014).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Feeding with the preparation was started three weeks before the calving and ended 10 weeks after the calving. The results revealed that DFM had a positive effect on digestibility of the fodders in the digestive tract (Al Zahal et al, 2014).…”
Section: Introductionmentioning
confidence: 91%
“…Intensive production technology is accompanied by tension in the functions of all of the organs, and the most intense period that determines the health and productivity of the animals is the transitional period. Therefore, Al Zahal et al (2014) performed and analysis of influence of microbiological preparation (DFM) on the consumption of dry matter, milk yield, milk components, the morbidity rate and metabolites in the blood of dairy cattle in the transitional period and also digestion of the nutrients. Feeding with the preparation was started three weeks before the calving and ended 10 weeks after the calving.…”
Section: Introductionmentioning
confidence: 99%
“…Probiyotiklerin çiftlik hayvanlarında kullanımlarına yönelik birçok araştırma mevcut olmakla birlikte, bu çalışmada daha çok süt sığırı yetiştiriciliğindeki yeri ve önemi üzerinde durulmuştur. Bilindiği gibi, hayvan beslemede yem katkı maddesi olarak kullanılan probiyotikler süt sığırlarında yemden yararlanma ve verim performansı artışı, yüksek süt veriminin sağlanması için kuru dönemde karşılaşılan problemlerinin önüne geçilmesi, buzağılama dönemindeki metabolik hastalıkların ve ishal vakalarının azaltılması ile çeşitli stres faktörlerinin olumsuz etkilerinin ortadan kaldırılması gibi çeşitli kullanım alanlarına sahiptir (35)(36)(37)(38)(39)(40)(41)(42).…”
Section: Süt Sığırlarında Kullanım Alanlarıunclassified
“…While the survival and proliferation of these organisms in the rumen and the effect of these probiotic bacteria on rumen digestive processes has been largely under-represented in the scientific literature, the probiotic effects of yeasts (S. cerevisiae) has been more extensively assessed 33,34 . Results can be highly variable between studies, however several investigations have established that the provision of these commercially available probiotics is most useful when applied to young ruminants to accelerate the establishment of a healthy gastrointestinal microflora 35,36 . Probiotics may be used to exclude undesirable zoonotic pathogens such as Escherichia coli O157 from establishing in the ruminant gastrointestinal tract and may also impact on the ruminant host immune system and feed breakdown efficiency [36][37][38] .…”
Section: Feed Supplements Probiotics and Direct Fed Microbialsmentioning
confidence: 99%